Pertumbuhan dan Hasil Tanaman Kacang-kacangan dengan Pupuk Organik Cair berbagai Sisa Buahan - Achadi, Teguh; Haikal, Umair; Angraini, Lili; Ghifari, Muhammad Al; Yakup, Yakup; Marlina, Marlina; Warsito, Warsito (Seminar Nasional Lahan Suboptimal, 2022)
Achadi T, Haikal U, Angraini L, Ghifari MA, Yakup Y, Marlina M, Warsito W. 2022. Growth and yield of legume crops with liquid organic from various fruit residues. In : Herlinda S et al. (Eds), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 217-225. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Liquid organic fertilizer is the result from decomposition of organic matter derived from animals or plants. Liquid organic fertilizer is made from damaged or rotten fruit and from the skin of the fruit (banana, papaya, pineapple and a mixture of all three). This study aimed to determine the effect of liquid organic fertilizer (POC) on the growth and yield of legumes (Soybeans, Peanuts and Green Beans). This research was conducted from July to October 2022. This study used a Complete Randomized Design with eight treatments including controls, namely A (recommended NPK fertilizer), B (POC of banana fruit residue), C (POC of pineapple fruit residue), D (POC sis of Papaya fruit), E (POC of banana + pineapple fruit residue), F (POC of banana + papaya fruit residue), G (POC of pineapple fruit residue + papaya) and H (remaining banana fruit + pineapple + papaya). The results showed that liquid organic fertilizer were not significantly different the recommended NPK fertilizer to all variables with out number of branches and productive branch of Soybeans and numbers of branches of Peanuts so hope that liquid organic fertilizer from Various Fruit Residues increase to Yield of Legume Crops (Soybeans, Peanuts and Green Beans).